Stings of the missing string: missing Copper T thread - Junnare, Ketaki K.; Sawaskar, Saloni; Shekhawat, G. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Missing CuT thread is a worrisome complaint for a woman. The string may be curled in or the Cu T might have expelled or migrated. Methods: It was a retrospective study. Authors collected the data between January 2017 to December 2017. Data was collected from OPD, OT register and Indoor patient record file. The objective was to ascertain the symptomatology, type of insertion, investigations and mode of retrieval of CuT. Results: There were 63 cases of missing CuT thread, out of which, 42 were postpartum. 33 patients were asymptomatic. Irregular vaginal bleeding (19 patients) was commonest complaint, followed by abdominal pain (10 patients). Pregnancy was detected in one patient. Transvaginal ultrasonography (TVS) detected intrauterine location of CuT in 60 cases. X-ray abdomen erect was needed in 3 cases, which detected intra-abdominal migration of CuT in two cases. CuT was expelled in third case. In 31 patients, CuT was removed by artery forceps in OPD. In 17 cases, hysteroscopic Copper T removal was needed. Two cases with migrated CuT underwent laparoscopy for retrieval of CuT. One patient had to be converted to laparotomy to rule out bowel injury. Conclusions: Missing CuT thread is commonest with postpartum IUCD. TVS should be first investigation in missing CuT thread. X-ray abdomen is needed only if CuT is not visualized on TVS. Hysteroscopy can be used in patients where CuT retrieval with artery forceps fails. Laparoscopy and laparotomy may be required in migrated CuT cases.